2006
DOI: 10.1038/sj.npp.1301004
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Immune Challenge: Defining a Critical Window for Effects on Adult Responses to Immune Challenge

Abstract: Many aspects of mammalian physiology are functionally immature at birth and continue to develop throughout at least the first few weeks of life. Animals are therefore vulnerable during this time to environmental influences such as stress and challenges to the immune system that may permanently affect adult function. The adult immune system is uniquely sensitive to immune challenges encountered during the neonatal period, but it is unknown where the critical window for this programming lies. We subjected male S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 38 publications
9
85
1
Order By: Relevance
“…This time window is similar to the period we previously observed for other physiological changes caused by postnatal LPS (Spencer et al, 2006b). Interestingly, this is also the time when long-term potentiation-induced plasticity first becomes apparent (e.g., P7) and shows maximum responsivity (e.g., P15) (Harris and Teyler, 1984).…”
Section: Discussionsupporting
confidence: 53%
“…This time window is similar to the period we previously observed for other physiological changes caused by postnatal LPS (Spencer et al, 2006b). Interestingly, this is also the time when long-term potentiation-induced plasticity first becomes apparent (e.g., P7) and shows maximum responsivity (e.g., P15) (Harris and Teyler, 1984).…”
Section: Discussionsupporting
confidence: 53%
“…In this laboratory, we have observed body weight changes under the condition of experimental colitis, where P14 LPS-treated rats, as adults, lost considerably more of their body weight than did neonatally saline-treated controls in response to trinitrobenzene sulfonic acid (TNBS)-colitis (56). However, we have not seen similar changes with a P14 immune challenge under other experimental conditions (57). These observations leave some important questions unanswered.…”
mentioning
confidence: 46%
“…Ears were clipped for identification and the pups were returned to the dam. We have previously shown that both saline-and LPS-injected pups receive similar maternal attention (Spencer et al, 2006b), thus minimizing the possibility that maternal care is the basis for differences between LPS-and salinetreated animals. At P21, male rats were selected, weaned, and housed four per cage until they reached 2 months of age, at which time they were housed two per cage for the remainder of the experiments.…”
Section: Methodsmentioning
confidence: 99%